2020
DOI: 10.1002/agj2.20270
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of intercropped wheat in jujube‐ and walnut‐based agroforestry systems in southern Xinjiang Province, China

Abstract: Agroforestry is widely practiced in China and has the benefit of diversifying agricultural production and enhancing natural resource utilization; however, these systems create competition for light between trees and understory crops. We investigated the effects of shading by jujube (Zizyphus jujuba Mill.) and walnut (Juglans regia L.) trees on the yield and quality of intercropped wheat (Triticum aestivum L.) in agroforestry systems in southern Xinjiang Province, China. In the walnut–wheat intercropping system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Significant variations in both protein and amino acid contents were observed in [62] through six quinoa varieties cultivated under different pedoclimatic conditions. Similar findings were reported by [22] on wheat in olive-based agroforestry (4%), [63] on wheat in jujube-and walnut-based agroforestry, and [64] on soybean under Aonla trees. In [25,51], positive correlations between shade and protein content were reported.…”
Section: Seed Nutritional Qualitysupporting
confidence: 83%
“…Significant variations in both protein and amino acid contents were observed in [62] through six quinoa varieties cultivated under different pedoclimatic conditions. Similar findings were reported by [22] on wheat in olive-based agroforestry (4%), [63] on wheat in jujube-and walnut-based agroforestry, and [64] on soybean under Aonla trees. In [25,51], positive correlations between shade and protein content were reported.…”
Section: Seed Nutritional Qualitysupporting
confidence: 83%
“…(2017) indicated that the irradiance was reduced by 60% below crowns of shade trees, but coffee ( Coffea L.) light‐use efficiency increased by 50%. In our previous studies we also found that the mean PAR in the understory of walnut trees was reduced by 72.4–79.7%, whereas the net photosynthetic rate was only decreased by 45.8–49.6%, as compared to wheat grown in monoculture (Qiao et al., 2020). Meanwhile in the present study, we also could see understory mean daily PAR decreased by 87.0, 73.7, and 52.3% (Figure 4), and Pn of flag leaves were decreased by 31.6, 14.1, and 3.3% (Figure 5), respectively, at distances of 1.5, 2.5, and 3.5 m to a row of 10‐yr‐old trees at the filling stage.…”
Section: Discussionmentioning
confidence: 70%
“…And this reduction was related to reductions in spike number, grains per spike, and thousand‐grain weight (Table 4; Supplemental Table S3). The declines in the spike number, grains per spike, and thousand‐grain weight were caused by the reductions in tillers, florets and spikelets per spike, and grain‐filling rates, respectively, in agroforestry systems (Qiao et al., 2020). This was also partly confirmed by Inurreta‐Aguirre et al.…”
Section: Discussionmentioning
confidence: 99%
“…Light competition between trees and crops is the predominant factor limiting crop growth (Dupraz et al, 2018). Wheat in the PWW system can receive higher light intensity and longer light duration for growth due to the widely spaced arrangement of poplars (Kittur et al, 2016; Qiao et al, 2020). Therefore, the PWW system exhibited higher wheat FRLD in comparison with the PWN system.…”
Section: Discussionmentioning
confidence: 99%